A method for preparing activated carbon fibers with high specific surface area and high microporosity by physical activation and applications thereof

CN116732647BActive Publication Date: 2026-10-09DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310553918.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-16
Publication Date
2026-10-09
Estimated Expiration
2043-05-16

AI Technical Summary

Technical Problem

物理活化法制备的活性炭比表面积和微孔率呈现出明显的trade-off效应,当活化强度不足时,所得产物微孔率高但比表面积较低;当活化强度高时,比表面积大幅增加,但介孔和大孔增加,微孔率降低

Benefits of technology

[0013] The activated carbon fibers prepared using the above physical activation method have a microporosity greater than 85% and a specific surface area greater than 1900 m². 2 /g; and the microporosity and specific surface area of ​​activated carbon fibers prepared from pre-oxidized fibers with different oxygen mass contents are different.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116732647B_ABST
    Figure CN116732647B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing activated carbon fibers with high specific surface area and high microporosity by physical activation and application. The preparation method of the activated carbon fibers comprises the following steps: a pitch-based fiber yarn is subjected to an oxidation treatment to obtain a pre-oxidized yarn with different oxygen contents, the pre-oxidized yarn is carbonized under an inert atmosphere, the temperature is continuously increased to an activation temperature, activation gas is introduced for activation treatment, after the activation is completed, the inert gas is switched to and the pre-oxidized yarn is naturally cooled to room temperature, and the activated carbon fibers with high specific surface area and high microporosity are obtained. The oxygen content of the pitch-based fiber yarn is regulated by the oxidation treatment, so that the activated carbon fibers with high specific surface area and high microporosity are prepared, and the obtained activated carbon fibers can be used as excellent radioactive iodine vapor adsorption materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of carbon material preparation and environmental protection technology, and in particular to a method for preparing activated carbon fibers with both high specific surface area and high microporosity through physical activation. Background Technology

[0002] Energy and the environment have always been topics of concern. Due to rapid global economic development, the demand for energy has increased accordingly. Coal and oil are non-renewable energy sources, and overexploitation inevitably leads to energy consumption and environmental damage. Furthermore, climate change necessitates a reduction in traditional energy consumption. Therefore, developing new and renewable energy sources is crucial for sustainable energy development. Nuclear power plants, which utilize nuclear energy for power generation, are among the most efficient energy sources, with almost zero greenhouse gas emissions. The development of nuclear energy has become a hot topic, but the safe disposal of nuclear waste containing radioactive materials, especially radioactive iodine, is a major issue concerning the use of nuclear energy.

[0003] Among existing iodine adsorbents, metal-organic frameworks (MOFs), silver-exchanged zeolites, and covalent organic frameworks are favored for their excellent adsorption capacity for iodine vapor. However, silver-based adsorbents are expensive, and MOFs and covalent organic frameworks have complex preparation processes and unstable structures, which limits their application to some extent. Porous carbon, on the other hand, is one of the most promising adsorbents in the field of radioactive iodine vapor adsorption due to its low cost, large specific surface area, tunable pore size, and excellent thermal stability. Studies have shown that the microporosity and specific surface area of ​​porous carbon have a significant impact on its radioactive iodine vapor adsorption capacity. Porous carbon materials with both high specific surface area and high microporosity have well-developed micropores, excellent adsorption performance, strong adsorption capacity, and a huge specific surface area, showing great application potential in air and water purification, food and pharmaceutical decolorization, and catalyst supports. Therefore, in recent years, the preparation of porous carbon materials with both high specific surface area and high microporosity has become a hot topic.

[0004] Currently, there are reports on the preparation of porous carbon materials with high specific surface area and high microporosity using chemical activation methods. Patent CN202111608367.8 describes the preparation of activated carbon with high microporosity and high specific surface area using a two-step chemical activation method involving low and high temperatures, using high-carbon raw materials. Patent CN200810050249.8 proposes the preparation of porous carbon materials with high specific surface area and narrow pore distribution using pine needles (a biomass material) as raw material, by adjusting the amount of activator, activation temperature, and activation time. Patent CN202210814819.6 proposes the preparation of hierarchical porous carbon materials for efficient iodine capture using aniline, phytic acid, and oxidants through polymerization, carbonization, and chemical activation. However, research on the preparation of porous carbon materials with high specific surface area and high microporosity using environmentally friendly and low-cost physical activation methods is rarely reported. Physical activation refers to the process in which carbon atoms in the carbon precursor undergo a gasification reaction with CO2, water vapor, or air, thereby generating a large number of pores and a high specific surface area. The specific surface area and microporosity of activated carbon prepared by physical activation method exhibit obvious trade-off effects. When the activation intensity is insufficient, the obtained product has high microporosity but low specific surface area; when the activation intensity is high, the specific surface area increases significantly, but mesopores and macropores increase, and microporosity decreases. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention aims to provide a method for preparing activated carbon fibers with both high specific surface area and high microporosity through physical activation.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing activated carbon fibers with high specific surface area and high microporosity through physical activation, comprising the following steps:

[0007] The pitch-based fiber is oxidized to obtain a pre-oxidized fiber with an oxygen content of 10-25%. It is then carbonized in an inert atmosphere, heated to the activation temperature, and activated by introducing an activation gas. After activation, the gas is switched to an inert gas and allowed to cool naturally to room temperature to obtain the activated carbon fiber with high specific surface area and high microporosity.

[0008] In the above technical solution, preferably, the oxidation treatment is gas-phase oxidation or liquid-phase oxidation; the gaseous oxidant for gas-phase oxidation is air, ozone, oxygen, or nitrogen dioxide, with a flow rate of 0.5-3 L / min, a temperature of 150-400℃, a heating rate of 1-10℃ / min, and a treatment time of 30-180 min; the liquid oxidant for liquid-phase oxidation is nitric acid, hydrogen peroxide, sodium hypochlorite, or ammonium persulfate, with a mass fraction of 8-30% for the liquid oxidant solution, a mass ratio of asphalt-based fiber to liquid oxidant of 1:1-10, and a treatment time of 30-120 min;

[0009] In the above technical solution, preferably, the inert atmosphere is one or a mixture of two or more of nitrogen, argon, and helium; the flow rate of the inert gas is 50-150 ml / min.

[0010] In the above technical solution, preferably, the heating rate of the carbonization treatment is 2-10℃ / min; the temperature of the carbonization treatment is 300-700℃; and the carbonization treatment time is 0-150min.

[0011] In the above technical solution, preferably, the activating gas is one or a mixture of two or more of carbon dioxide, water vapor, and air; the flow rate of the activating gas is 0.01-0.20 kg / h.

[0012] In the above technical solution, preferably, the activation treatment heating rate is 5-20℃ / min; the activation treatment temperature is 750-900℃; and the activation treatment time is 100-300min.

[0013] The activated carbon fibers prepared using the above physical activation method have a microporosity greater than 85% and a specific surface area greater than 1900 m². 2 / g; and the microporosity and specific surface area of ​​activated carbon fibers prepared from pre-oxidized fibers with different oxygen mass contents are different.

[0014] The beneficial effects of this invention are as follows: the specific surface area and microporosity of activated carbon are highly dependent on the selected precursor. Compared with existing physical activation techniques for preparing porous carbon, this invention addresses the trade-off effect of specific surface area and microporosity in activated carbon fibers by proposing an oxidation method to control the oxygen content of pitch-based fibers, thereby preparing activated carbon fibers with both high specific surface area and high microporosity. This invention discovers that pitch-based fibers, after gas-phase or liquid-phase oxidation treatment, yield pre-oxidized fibers with an oxygen content of 10-24%. These pre-oxidized fibers, after physical activation, can achieve the preparation of activated carbon fibers with both high specific surface area and high microporosity. The method provided by this invention is simple to operate, has low process costs, requires minimal equipment investment, has a wide range of applications, is easy to scale up industrially, and the resulting porous carbon with high specific surface area and high microporosity exhibits strong adsorption capacity for radioactive iodine vapor. Attached Figure Description

[0015] Figure 1 The nitrogen adsorption-desorption curves of the activated carbon fibers obtained in Examples 2 and 6 of this invention are shown below.

[0016] Figure 2 The DFT pore size distribution diagrams of the activated carbon fibers obtained in Examples 2 and 6 of this invention are shown below. Detailed Implementation

[0017] The following examples further illustrate specific implementations of the present invention, but the implementation and protection of the present invention are not limited thereto. It should be noted that any processes not specifically described below are those that can be implemented or understood by those skilled in the art by referring to existing technology. Reagents or instruments whose manufacturers are not specified are considered to be conventional products that can be purchased commercially.

[0018] Example 1

[0019] 20g of pitch-based fiber filaments were placed in a muffle furnace, and oxygen was introduced at a rate of 0.5L / min. The temperature was increased to 150℃ at a rate of 10℃ / min and held for 30min to obtain pitch-based pre-oxidized fiber with an oxygen content of 10.12%. 12g of the 10.12% oxygen-content pitch-based pre-oxidized fiber was placed in a tube furnace, and nitrogen was introduced at a rate of 50ml / min. The temperature was increased to 300℃ at a rate of 2℃ / min and held for 150min. The temperature was then increased to 900℃ at a rate of 20℃ / min. Carbon dioxide was introduced at a flow rate of 0.01kg / h and held for 300min. Afterward, nitrogen was introduced at a flow rate of 50ml / min, and the furnace was allowed to cool naturally to room temperature. The resulting porous carbon material, ACF-1, had a specific surface area of ​​2019.501m². 2 / g, with a microporosity of 88.639%.

[0020] Example 2

[0021] 20g of pitch-based fiber filaments were placed in a muffle furnace, and air was introduced at a rate of 2L / min. The temperature was increased to 200℃ at a rate of 2℃ / min and held for 120min to obtain pitch-based pre-oxidized fiber with an oxygen content of 13.88%. 12g of the pitch-based pre-oxidized fiber with an oxygen content of 13.88% was placed in a tube furnace, and nitrogen gas was introduced at a rate of 60ml / min. The temperature was increased to 900℃ at a rate of 10℃ / min, then water vapor was introduced at a flow rate of 0.045kg / h, and the temperature was held for 150min. Afterward, nitrogen gas was introduced at a flow rate of 60ml / min, and the furnace was allowed to cool naturally to room temperature. The resulting porous carbon material ACF-2 has a specific surface area of ​​2300.730 m². 2 / g, with a microporosity of 89.167%.

[0022] Example 3

[0023] 20g of pitch-based fiber filaments were placed in a muffle furnace, and nitrogen dioxide was introduced at a rate of 3L / min. The temperature was increased to 400℃ at a rate of 1℃ / min and held for 180min to obtain pitch-based pre-oxidized fiber with an oxygen content of 17.50%. 12g of the pitch-based pre-oxidized fiber with an oxygen content of 17.50% was placed in a tube furnace, and argon gas was introduced at a rate of 150ml / min. The temperature was increased to 700℃ at a rate of 10℃ / min and held for 60min. The temperature was then increased to 900℃ at a rate of 10℃ / min, and water vapor at a flow rate of 0.045kg / h was introduced. The temperature was held for 150min, and then argon gas was introduced at a rate of 150ml / min for natural cooling to room temperature. The resulting porous carbon material ACF-3 has a specific surface area of ​​2182.421m². 2 / g, with a microporosity of 88.502%.

[0024] Example 4

[0025] 20g of pitch-based fiber filaments were placed in a muffle furnace, and ozone was introduced at a rate of 2L / min. The temperature was increased to 300℃ at a rate of 2℃ / min and held for 120min to obtain pitch-based pre-oxidized fiber with an oxygen content of 23.82%. 12g of the pitch-based pre-oxidized fiber with an oxygen content of 23.82% was placed in a tube furnace, and helium gas was introduced at a rate of 60ml / min. The temperature was increased to 900℃ at a rate of 5℃ / min, then switched to air at a flow rate of 0.2kg / h and held for 150min. Afterward, helium gas was introduced at a flow rate of 60ml / min and the furnace was allowed to cool naturally to room temperature. The resulting porous carbon material, ACF-4, had a specific surface area of ​​2041.479m². 2 / g, with a microporosity of 89.594%.

[0026] Example 5

[0027] 20g of pitch-based fiber filaments were immersed in 250g of 8% nitric acid solution for 30min, then filtered and rinsed with deionized water to remove the nitric acid, yielding pitch-based pre-oxidized fiber with an oxygen content of 15.36%. 12g of the 15.36% oxygen-content pitch-based pre-oxidized fiber was placed in a tube furnace, and nitrogen gas was introduced at a rate of 60ml / min. The temperature was increased to 900℃ at a rate of 10℃ / min, then replaced with water vapor at a flow rate of 0.045kg / h, and held at that temperature for 170min. Afterward, the temperature was naturally cooled to room temperature at a rate of 60ml / min. The resulting porous carbon material, ACF-5, had a specific surface area of ​​2238.213m². 2 / g, with a microporosity of 90.412%.

[0028] Example 6

[0029] 20g of pitch-based fiber filaments were immersed in 650g of a 30% ammonium persulfate solution for 50min, then filtered and rinsed with deionized water to remove the ammonium persulfate, yielding pitch-based pre-oxidized fiber with an oxygen content of 13.45%. 12g of the 13.45% oxygen-content pitch-based pre-oxidized fiber was placed in a tube furnace, and nitrogen gas was introduced at a rate of 60ml / min. The temperature was increased to 900℃ at a rate of 10℃ / min, then water vapor was introduced at a flow rate of 0.045kg / h, and the temperature was maintained for 170min. Afterward, the temperature was naturally cooled to room temperature at a rate of 60ml / min. The resulting porous carbon material, ACF-6, had a specific surface area of ​​2532.010 m². 2 / g, with a microporosity of 87.500%.

[0030] Example 7

[0031] 20g of pitch-based fiber filaments were immersed in 200g of a 10% hydrogen peroxide solution for 60min, then filtered and rinsed with deionized water to remove the hydrogen peroxide, yielding pitch-based pre-oxidized fiber with an oxygen content of 19.60%. 12g of the 19.60% oxygen-content pitch-based pre-oxidized fiber was placed in a tube furnace, and nitrogen gas was introduced at a rate of 60ml / min. The temperature was increased to 900℃ at a rate of 10℃ / min, then water vapor was introduced at a flow rate of 0.045kg / h, and the temperature was maintained for 170min. Afterward, the temperature was naturally cooled to room temperature at a rate of 60ml / min. The resulting porous carbon material, ACF-7, has a specific surface area of ​​2254.970m². 2 / g, with a microporosity of 88.093%.

[0032] Example 8

[0033] 20g of pitch-based fiber filaments were immersed in 200g of a 10% sodium hypochlorite solution for 120min, then filtered and rinsed with deionized water to remove the sodium hypochlorite, yielding pitch-based pre-oxidized fiber with an oxygen content of 24.56%. 12g of the filament pre-oxidized fiber with an oxygen content of 24.56% was placed in a tube furnace, and nitrogen gas was introduced at a rate of 60ml / min. The temperature was increased to 900℃ at a rate of 10℃ / min, then water vapor was introduced at a flow rate of 0.045kg / h, and the temperature was maintained for 170min. Afterward, the temperature was naturally cooled to room temperature at a rate of 60ml / min. The resulting porous carbon material, ACF-8, had a specific surface area of ​​1927.172m². 2 / g, with a microporosity of 85.936%.

[0034] Table 1. Pore structure parameters of activated carbon fibers prepared in Examples 1-8

[0035]

[0036] Application Example 1

[0037] The activated carbon fibers obtained in Examples 2 and 6 were subjected to iodine vapor adsorption tests. The method involved placing excess iodine in a desiccator, placing 100 mg of sample at the bottom of a 20 ml weighing bottle, opening the bottle, placing it in the desiccator, tightening the desiccator, and then placing it in a 75°C oven. The bottle was weighed at regular intervals until a constant weight was achieved. The iodine vapor adsorption content of the sample was determined by gravimetric method. An empty weighing bottle of the same specifications was used as a reference during the test. The calculation formula is as follows: Q = (m2 - m1 - M2 + M1) / m1, where Q (g / g) is the amount of iodine adsorbed, m1 (g) and m2 (g) are the weights of the sample before and after iodine adsorption, respectively, and M1 (g) and M2 (g) are the corresponding reference bottle masses.

[0038] Table 2. Iodine vapor adsorption capacity of AC-1, AC-2 and AC-3

[0039]

Claims

1. A method for preparing activated carbon fibers with both high specific surface area and high microporosity through physical activation, characterized in that: The method includes the following steps: The pitch-based fiber filaments are oxidized to obtain pre-oxidized filaments with an oxygen mass content of 10-25%. They are then carbonized in an inert atmosphere, heated to the activation temperature, and activated by introducing an activation gas. After activation, the gas is switched to an inert gas and allowed to cool naturally to room temperature to obtain the activated carbon fiber with high specific surface area and high microporosity. The oxidation treatment is either gas-phase oxidation or liquid-phase oxidation; the gaseous oxidant for gas-phase oxidation is air, ozone, oxygen, or nitrogen dioxide, with a flow rate of 0.5-3 L / min, a temperature of 150-400℃, a heating rate of 1-10℃ / min, and a treatment time of 30-180 min; the liquid oxidant for liquid-phase oxidation is nitric acid, hydrogen peroxide, sodium hypochlorite, or ammonium persulfate, with a mass fraction of 8-30% for the liquid oxidant solution, a mass ratio of pitch-based fiber filaments to liquid oxidant of 1:1-10, and a treatment time of 30-120 min; The carbonization process is carried out at a heating rate of 2-10℃ / min; the carbonization temperature is 300-700℃; and the carbonization time is 60-150min. The activating gas is one or a mixture of two or more of carbon dioxide, water vapor, and air; the flow rate of the activating gas is 0.01-0.20 kg / h. The activation treatment heating rate is 5-20℃ / min; the activation treatment temperature is 750-900℃; and the activation treatment time is 100-300min. The activated carbon fiber has a microporosity greater than 85% and a specific surface area greater than 1900 m². 2 / g; Pre-oxidized fibers with different oxygen content produce activated carbon fibers with different microporosity and specific surface area.

2. The method according to claim 1, characterized in that: The inert atmosphere is one or a mixture of two or more of nitrogen, argon, and helium; the flow rate of the inert gas is 50-150 mL / min.

3. The application of the activated carbon fiber prepared by the method according to claim 1 or 2, characterized in that, The activated carbon fiber is used for the adsorption of radioactive iodine vapor.

Citation Information

Patent Citations

  • High specific surface area and narrow pore distribution porous carbon material

    CN101214951A

  • A high-microporosity, high-specific-surface-area activated carbon and its preparation method

    CN114132925B

  • Graded porous carbon material for efficiently capturing iodine as well as preparation method and application of graded porous carbon material

    CN115403042A

  • Asphalt-based carbon fiber and preparation method thereof

    CN112522810A